Farm related and wild animals inflicted injuries related to orthopaedics in Eastern Nepal: Epidemiology and prospects for control (Health Renaissance, 2017)
Background: Farm related and animal inflicted injuries are common in Nepal.Objective: To assess the pattern of farm related and wild animal inflicted injury in patients presenting to B.P. Koirala Institute of Health Sciences. Method: This prospective observational study of farm related and wild animals inflicted injuries related to Orthopaedics, conducted from May 2005 to April 2007 at Department of Orthopaedics of B.P. Koirala Institute of Health Sciences Dharan, Nepal, consisting of 87 patients admitted to the Orthopaedic ward of BPKIHS, is presented. The preformed structured proforma were used to record the data and, later those records were analyzed.Result: Altogether 78 domestic related injuries and 9 wild animal related injuries were recorded in the recruitment a period of one year. Twenty-three femoral fractures, 14 humeral fractures, 11 cervical spine injuries, 10 leg bone fractures, 9 forearm fractures were found. Fall from buffalo, hit by buffalo were common cause of injuries in domestic related injuries whereas hit / kick by elephant, attack by bear were causes of wild animal related injuries. All adolescents and adults, irrespective of age or sex, should be the target groups for community education and intervention programs for prevention of such injuries.Conclusion: Femoral fractures were the most common bone injury among farm related and animal inflicted injury.Health Renaissance 2015;13(2): 66-71